Expression of testicular phosphorylated proteins in types 1 and 2 diabetes mellitus in mice: An experimental study - Apichakan Sampannang; Supatcharee Arun; Jaturon Burawat; Wannisa Sukhorum; Sitthichai Iamsaard (Shahid Sadoughi University of Medical Sciences, 2019)
Background Types 1 and 2 diabetes mellitus (DM) are known to be the cause of sub/infertility. However, the comparisons of potential markers in spermatogenesis and steroidogenesis in DM males have never been elucidated. Objective This study aimed to examine the expressions of tyrosine-phosphorylated and steroidogenic acute regulatory (StAR) proteins in testis of DM mice. Materials and Methods Fifty-six male C57BL/6 mice were divided into four groups (n░=░14/ each): control of MLD-STZ (multiple low doses of streptozotocin), MLD-STZ, control of HFD-STZ (high-fat diet with STZ), and HFD-STZ. MLD-STZ mice (type 1 DM) were intraperitoneally (i.p.) injected with STZ at 40░mg/kg BW for five days. HFD-STZ mice (type 2 DM) received an HFD for 14 days and i.p.-induced by STZ at 85░mg/kg BW and fed with HFD. At the end of the experiment (days 36 and 72), the expressions of phosphorylated proteins and StAR were examined. Results Tyrosine phosphorylated proteins were localized in late spermatids, luminal fluid, and Leydig cells. The intensities of phosphorylated 110, 85, 72, 60, and 55░kDas were lower in the 36 day-DM mice. Although such intensities were present in both groups, only 85░kDa in the MLD-STZ mice was higher in HFD mice at 72 days. StAR expressions in both groups were decreased than that of the controls. Conclusion Decreased expressions of StAR and tyrosine-phosphorylated proteins may be directly involved in low testosterone levels and impaired spermatogenesis. These findings support the notion that both DM types play a role in male infertility.